PENCETAKAN RAHANG PASIEN PADA PEMBUATAN GIGI TIRUAN SEBAGIAN LEPASAN BERBAHAN FLEXY DI DESA BARANIA KABUPATEN SINJAI BARAT - Ariyani Goeliling (CV. CAHAYA BINTANG CEMERLANG, 2024)
Ariyani Goeliling, 2023. Impression of the patient's jaw in the manufacture of flexy partial dentures in Barania Village, West Sinjai Regency.Common symptoms seen after losing one or more teeth are migration of teeth, tilted shape, totation and extrusion. Diastema, food impaction and occlusal trauma to the area of the remaining teeth. Impaired mastication of the posterior teet, aesthetic and speech disturbances of anterior teeth. Purpose : The purpose of this community service activity is to increase public knowledge about the importance of knowing the impact thar will arise and increase the confidence of the people in Barania Village, West Sinjai Regency, South Sulawesi Province. Problem : The problem experienced is that many people really need dental and oral health services especially denture fiiting. However, the services are difficult to obtain because of the distance from Barania Village to the nearest health facility -+ 10 km. Solution to the problem : denture fitting is a way to solve dental and oral problems. Outcome and target : all pepople know about the impact that will arise if they don’t use dentures in edentulous areas and furthes increase the self confidence of the people after wearing dentures in Barania Village, West Sinjai Regency, South Sulawesi Province.